(untitled) (Thailand, 1997)
The report provides a presentation of characterisation, ultilisation and maintenance of biological diversity for the diversification and sustainability of catfish culture in South-East Asia
Keywords: Nuôi cá da trơn,Catfish culture,Biodiversity conservation